Vol. 92 : Thermophysical Basis of Energy Technologies (TBET-2016) Proceedings of the Conference, October 26-28, 2016, Tomsk, Russia - Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Zhdanova A. O. Alena Olegovna (2017, 2017)
Title screen